Analisis Minat dan Motivasi Belajar, Pemahaman Konsep dan Kreativitas Siswa terhadap Hasil Belajar Selama Pembelajaran dalam Jaringan - Susi Sihombing; Hizkia Ronaldus Silalahi; Jonas Ramza Sitinjak; Hardi Tambunan (Jurnal Pendidikan Matematika:Judika Education, 2021)
The purpose of this study was to investigate the relationship between the variables of interest and creativity, conceptual understanding and motivation on mathematics learning outcomes for students of class X SMA Medan City. This research is an ex-post facto research which is corrective. The study population was 180 students from two public and two private high schools taken in clusters from several secondary schools in the city of Medan. The sampling technique uses the Slovin formula. The results of the analysis showed that interest in learning mathematics obtained an average score of 76.84 from a maximum value of 100 with a standard deviation of 7.8 and a variance of 61.67. Furthermore, hypothesis testing using multiple linear regression analysis. In conclusion, interest in learning mathematics has an influence on students' mathematics learning outcomes, creativity in learning mathematics has no effect on students' mathematics learning outcomes, mathematics learning motivation has an influence on students' mathematics learning outcomes and understanding of mathematics learning concepts has an influence on mathematics learning outcomes for class X students Medan City High School. Keywords: Geometry, Learning Outcomes, Student Creativity, Interests, Motivation, Concept Understanding.